Lekamer Fortir Cookies as Snack Alternative for Malnourished Toddlers - Bakara, Tiar Lince; Rumida, Rumida; Nasution, Erlina; Siahaan, Ginta (Indonesian Journal of Human Nutrition, 2023)
Cookies serve as an alternative snack option and an additional food source for toddlers. These cookies are widely enjoyed due to their taste, soft, and crunchy texture. This study aimed to analyze the chemical and organoleptic quality of Lekamer Fortir cookies, made from local food ingredients consisting of catfish, forte, oyster mushrooms, and red beans. This study used ANOVA test and analyzed the chemical, physical, and sensory quality of cookies, exploring their potential to prevent malnutrition. The selected cookies, formula D, consisted of 40 grams of red bean flour, 10 grams of oyster mushroom flour, 40 grams of catfish flour, and 10 grams of tempeh formula flour. Organoleptic test results showed an average score of 3.79, indicating a strong preference. Further examination of the nutritional composition of Formula D revealed that carbohydrates, protein, fat, and fiber were below 100% of the 2019 Recommended Daily Allowance (AKG) requirement. In contrast, calcium, zinc, and iron (Fe) content exceeded 100% of the 2019 AKG requirement. The results of the panelists’ preference for cookies using red bean flour, catfish flour, white oyster mushroom flour, and forte showed no significant differences in color, texture, and taste in each sample.